Safety and Effectiveness of Ninjin'yoeito: A Utilization Study in Elderly Patients - Suzuki, Shinichi; Aihara, Fumitaka; Shibahara, Miho; Sakai, Katsutaka (Frontiers in Nutrition, 2019)
Post-marketing surveillance studies of traditional Japanese medicine in Japan are limited, and currently there are no data for Ninjin'yoeito, which is often used for the elderly because of its efficacy. In this study, we aimed to investigate the post-marketing safety and efficacy of Ninjin'yoeito in elderly patients over 65 years of age in clinical practice in Japan. This survey was an open-label, non-comparative, prospective, multicenter, post-marketing survey conducted at 383 centers between February 2016 and March 2017. In the safety analysis of 808 patients, adverse reactions were reported in 25 patients (3.1%), most of whom had gastrointestinal disorders (2.1%). In the efficacy analysis, Ninjin'yoeito was found to significantly improve visual analog scale scores in fatigue/malaise and anorexia at weeks 8, 16, and 24, and weeks 8 and 24 after commencement of treatment, respectively. In addition, the Basic Checklist created by the Ministry of Health, Labor and Welfare of Japan was used as a secondary survey item. The proportion of patients expected to require nursing care significantly decreased after 24 weeks compared with the baseline in four domains (activities of daily living, motor function, oral function, and depression). On the basis of physician assessment, Ninjin'yoeito was rated as “effective” or “moderately effective” in 486 (90.5%) of 537 cases. As the checklist contains many aspects of frailty, Ninjin'yoeito might be beneficial in preventing frailty. The findings of the present study indicate the safety of Ninjin'yoeito in aged patients, although further integrated clinical trials are necessary to examine its efficacy.